Analysis of Students’ Errors in Geometry and Measurement in the Subject of Mathematics at Elementary Grades: A Study from the Mountainous Region of Pakistan - Pervaiz Alam, Sadia Bhutta, Sohail Ahmad, (JSE, 2024)
Geometry and Measurement (GM) is one of the essential aspects of mathematics that improves students’ various skills including visualization, critical thinking, problem-solving, and deductive reasoning. More importantly, GM is not only connected with various other branches of mathematics but it is also coupled with numerous other disciplines. It plays a crucial role in our daily activities and its importance cannot be overemphasized. Despite being a crucial content domain of school mathematics, students’ low performance has remained a matter of concern around the globe, and Pakistan with no exception. Among other reasons, errors in GM play a crucial role in this regard, and it needs to be thoroughly investigated. Therefore, this study aimed to analyze errors in GM of students (n=1006) enrolled in elementary grades (5, 6, and 8) in public and private schools of Gilgit-Baltistan. Students' responses to the items of GM were analyzed by identifying the most difficult items and discussing the types of errors with viable reasons. The results depict that the students of grade 5 and 6 found it very difficult to calculate the perimeter of a given rectangle and draw parallel line, respectively. Whereas, grade 8 students found the measurement of angles in a triangle and calculation of the area of a 2D shape the most difficult items. The paper speculates possible reasons for these errors and proposes recommendations for the relevant stakeholders.